Recent Trends in Intelligent and Emerging Systems - Sarma, Kandarpa Kumar (Springer, 2015)
It is a compilation of research works related to intelligent and emerging system design using a range of tools including soft-computation. The book includes reviews, actual designs, research works, discussion and experimental results related to works in the areas of communication, computation, vision sciences, bio-inspired system design, social dynamic, related process design, etc. The audience of this book is expected to be researchers who deal with intelligent and emerging system design through mathematical and computational modeling and experimental designs. Specifically, audiences that are broadly involved in the domains of electronics and communication, electrical engineering, mathematics, computer science, other applied informatics domains and related areas will find the book interesting. The works included in the book broadly covers all areas of Electronics and Communication Engineering and Technology, Soft-computational Applications, Human Computer Interactive Designs and Social and Economic Dynamics. The works included in the volume have been grouped into Communication, Biomedical and Social Science, HCI and Bio-inspired System Design, Speech Processing and Review totaling sixteen contributions.